Periphytic algae of two bioforms of macrophytes in a subtropical shallow lake of Argentina - Vallejos, Silvina Vanesa (2015)
Fil: Vallejos, Silvina Vanesa. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.